Phytochemical, pharmacognostic and antimicrobial evaluation in selected plant species - K.R. LEENA; V.K. RESHMA (International Journal of Pharma and Bio Sciences, 2018)
Plants are potent biochemist and have components of phytomedicine, since time immemorial. Man is able to obtain from them a wondrous assortment of industrial chemicals. The beneficial medicinal effects of plants such as healing and curing of disease is because of the presence of phytochemicals present in them. Phytochemical screening was done in selected five plant species for alkaloids, glycosides, flavonoids, phenols, steroids, tannins, etc.; histochemical study was conducted to locate the areas where these economically and biologically valuable phytochemicals were deposited, and the antimicrobial study helps to reveal the effect of these phytochemicals on selected microbes. However, depending on their solubility the action of these chemicals may vary, though some chemicals are common in all the species tested. The study revealed the presence of these biocompounds in these common plants and the reason for utilizing them in the home remedies, ethno and ayurvedic therapies.